Dynamic effects of Fto in regulating the proliferation and differentiation of adult neural stem cells of mice. (22nd November 2019) - Cao, Yuhang; Zhuang, Yingliang; Chen, Junchen; Xu, Weize; Shou, Yikai; Huang, Xiaoli; Shu, Qiang; Li, Xuekun
Abstract: N 6 -methyladenosine (m 6 A) modification of RNA is deposited by the methyltransferase complex consisting of Mettl3 and Mettl14 and erased by demethylase Fto and Alkbh5 and is involved in diverse biological processes. However, it remains largely unknown the specific function and mechanism of Fto in regulating adult neural stem cells (aNSCs). In the present study, utilizing a conditional knockout (cKO) mouse model, we show that the specific ablation of Fto in aNSCs transiently increases the proliferation of aNSCs and promotes neuronal differentiation both in vitro and in vivo, but in a long term, the specific ablation of Fto inhibits adult neurogenesis and neuronal development. Mechanistically, Fto deficiency results in a significant increase in m 6 A modification in Pdgfra and Socs5. The increased expression of Pdgfra and decreased expression of Socs5 synergistically promote the phosphorylation of Stat3. The modulation of Pdgfra and Socs5 can rescue the neurogenic deficits induced by Fto depletion. Our results together reveal an important function of Fto in regulating aNSCs through modulating Pdgfra / Socs5-Stat3 pathway.